Addressing the Misuse Potential of Life Science Research—Perspectives From a Bottom-Up Initiative in Switzerland - Oeschger, Franziska M.; Jenal, Ursula (Frontiers in Bioengineering and Biotechnology, 2018)
Codes of conduct have received wide attention as a bottom-up approach to foster responsibility for dual use aspects of life science research within the scientific community. In Switzerland, a series of discussion sessions led by the Swiss Academy of Sciences with over 40 representatives of most Swiss academic life science research institutions has revealed that while a formal code of conduct was considered too restrictive, a bottom-up approach towards awareness raising and education and demonstrating scientists’ responsibility towards society was highly welcomed. Consequently, an informational brochure on “Misuse potential and biosecurity in life sciences research” was developed to provide material for further discussions and education.